Regulação da reatividade vascular, dependente do estresse oxidativo e da via da PKD1, em ratos espontaneamente hipertensos - Hortelan, Michelle Rossana Martins (2023)
High blood pressure is one of the main causes of cardiovascular diseases. In the hypertension animal model, SHR, vascular dysfunction has been described as dependent on oxidative inactivation of nitric oxide (NO) due to higher vascular production of reactive oxygen species (ROS) dependent on NADPH oxidase (NOX). NOX's redox signaling pathways involve regulatory mechanisms, depending on second-mediated pathways messengers and intra- and extracellular signalers. Recently, importance has been given to the signaling pathway dependent on PKD1, an enzyme that belongs to the protein-kinase-dependent Ca2+-calmodulin superfamily. PKD1 has been related to vascular smooth muscle contraction and thus to the modulation of vascular reactivity. The hypothesis of this study is that the PKD1 pathway is involved in the regulation of vascular tone, in the SHR model, via NOXdependent oxidative stress. We used isolated aortic rings from Wistar and SHR rats to evaluate vascular reactivity mediated by α1 receptors and for angiotensin II (ATII). We performed concentration-response curves to phenylephrine (10−10 to 10−4 M) and angiotensin II (10−10 to 10−5 M) cumulatively, in the presence and absence of CID 3,2 μM, a selective inhibitor of PKD1, and Apokinin 30 μM, a NOX inhibitor. Vascular oxidative stress was analyzed by the thiobarbituric acid reactive species (TBARS) measurement technique, which allows us to evaluate lipid peroxidation and oxidative fluorescence of DHE in situ. Systolic blood pressure (SBP, mmHg) was measured by tail plethysmography 48 hours before the experiments. The results are described as mean ± SEM and were analyzed using: Student's t-test, one- or two-way ANOVA and Tukey's post-hoc test. The SHR group had lower body mass (Wistar (n=10) 313 ± 5.5 g vs SHR (n=10), 260 ± 8.5*g, *p<0.01) and higher SBP (Wistar: 130.0 ± 1.7 vs SHR: (n=10), 197.3 ± 2.5* mmHg, *p<0.01). There was no difference in HR values between the groups. The results collected so far demonstrated that the inhibition of PKD1, with ICD, did not modify the reactivity to phenylephrine in the Wistar group (Wistar Rmax: 114.4 ± 7.54 x Wistar-CID= 96.11 ± 13.7 % KCl). However, the incubation of aortic rings with CID reduced aortic reactivity to phenylephrine in the SHR group (SHR Rmax: 129.9 ± 8.28 x SHR-CID= 83.74 ± 9.3* % KCl, *p<0.01). The vasoconstrictor response to Angiotensin II was reduced in the presence of CID only in the Wistar group (Wistar Rmax: 52.5 ± 3.7 x Wistar-CID= 38.8 ± 6.4 % KCl, *p<0.01). There was no difference in Rmax responses between the CID and CID-Apokinin groups in the Wistar and SHR Documento assinado digitalmente conforme descrito no(s) Protocolo(s) de Assinatura constante(s) neste arquivo, de onde é possível verificar a groups. The vascular oxidative stress was not different between the groups, in the presence and absence of CID after incubation with Angiotensin II. However, the coincubation of CID and Apokinin, reduced the production of MDA in the SHR group. Based on the results found, we can accept our hypothesis that the PKD1 pathway participates in the regulation of aortic ring reactivity in the SHR and Wistar groups. We conclude that, while the PKD1 pathway seems to play a key role in the contraction of the aortic rings of the SHR group mediated by phenylephrine, the same pathway seems to be involved only in the response to angiotensin II in the Wistar group. Our hypothesis of the participation of oxidative stress in CID-mediated responses was rejected, since co-perfusation with Apokinin did not modify the CID-mediated response. This information is relevant to the understanding of the mechanisms involved in the regulation of blood pressure and may have important implications for the development of targeted therapies for the treatment of arterial hypertension.